A Systematic Study on the Utilization of Inorganic Salts as Catalyst for the Conversion of Xylose to Furfural - Soetedjo, Jenny N M; Rasrendra, Carolus B; Heeres, Hero J (IOP conference series. Materials Science and Engineering, 2020)
The utilization of biomass-waste such as sugar-bagasse,water-hyacynth and palm-oil-fiber as alternative sources for transportation fuels and platform-chemicals is a very active research field. Furfural(FF) is one-of-the-13top platform-chemicals that may be converted to derivatives such as furfuryl-alcohol,furoic-acid and furan with wide applications in the gasoline,diesel and jet-fuel blending-pool. Many studies have been conducted in the mechanism and the kinetics of FF-formation from xylose since the 1940s to maximize FF-yield and to reduce FF-decomposition to undesired-products. Previous studies showed that inorganic-salt gives positive effects on the FF-yield but systematic studies are lacking. Based on it, 60salts were screened in the hydrolysis of 0.1M xylose-aqueous-solution (T=180°C,90minutes,batch). The maximum FF-yield was 53mol% using 5mM-Fe2(SO4)3. The highest FF-selectivity was at 84mol% using 5mM-NaCl, though at low xylose-conversion(35 mol%-FF-yield). Some transition metal-chloride i.e.FeCl2,CuCl2,SnCl2 showed interesting FF-yields(48-50%) and selectivity(58-65%) indicating interesting roles of ion Fe3+ and Cl−. Subsequent studies of two salts i.e.Fe2(SO4)3 and FeCl3(5mM) in combination with HCl and H2SO4(0.1M) were investigated(0.1M-xylose,T=150°C,0-270 min). The result shows that salts increase no FF-yields for H2SO4 but increase the reaction-rate. In contrast, Fe2(SO4)3 increase no yield nor reaction-rate for HCl-catalyzed-system. In conclusion, the inorganic-salts catalyse xylose-conversion to furfural but best results were obtained using HCl without additional salts.